2014
DOI: 10.15398/jlm.v2i1.78
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of automatic updates of Roget’s Thesaurus

Abstract: Thesauri and similarly organised resources attract increasing interest of Natural Language Processing researchers. Thesauri age fast, so there is a constant need to update their vocabulary. Since a manual update cycle takes considerable time, automated methods are required. This work presents a tuneable method of measuring semantic relatedness, trained on Roget's Thesaurus, which generates lists of terms related to words not yet in the Thesaurus. Using these lists of terms, we experiment with three methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The lexical resource used for this purpose is OntoRo. This is an electronic resource based on Roget's Thesaurus [60] and has been employed in several other studies related to design [61] and information retrieval [62], [63]. Moreover, the use of OntoRo is also justified by linguistic studies [36], which have found that many of the names of image schemas correspond to Roget's subcategories.…”
Section: Ontology Of Image Schemasmentioning
confidence: 99%
“…The lexical resource used for this purpose is OntoRo. This is an electronic resource based on Roget's Thesaurus [60] and has been employed in several other studies related to design [61] and information retrieval [62], [63]. Moreover, the use of OntoRo is also justified by linguistic studies [36], which have found that many of the names of image schemas correspond to Roget's subcategories.…”
Section: Ontology Of Image Schemasmentioning
confidence: 99%